Steel bar and its manufacturing method

The development of a steel bar with a ferritic phase and a thick oxide scale, combined with a specific cold working process, addresses the challenge of achieving high axial yield strength and preventing surface defects, resulting in improved fatigue life and deformation resistance.

JP7669959B2Active Publication Date: 2025-04-30JFE STEEL CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022045025
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-22
Publication Date
2025-04-30
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

Conventional steel bar manufacturing methods struggle to achieve high axial yield strength while preventing surface dents and oyster defects, which are critical for improving fatigue life and resisting deformation under external stress loads.

Method used

A steel bar with a ferritic phase structure and an oxide scale thickness of 10 μm or more is developed, combined with a cold working process that maintains the oxide scale and applies strain to enhance axial yield strength to 400 MPa or more.

Benefits of technology

The proposed solution effectively increases the axial yield strength of steel bars and suppresses surface concaves caused by oyster defects, thereby enhancing fatigue life and resistance to deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669959000003
    Figure 0007669959000003
  • Figure 0007669959000004
    Figure 0007669959000004
  • Figure 0007669959000001
    Figure 0007669959000001
Patent Text Reader

Abstract

To provide: a bar steel capable of avoiding a recess of a surface layer due to a scratch, while enhancing yield strength in an axial direction; and a method for manufacturing the bar steel.SOLUTION: A bar steel has a component composition composed of, in terms of mass%, 0.01-1.15% of C, 0.01-2.50% of Si, 0.01-2.50% of Mn, 0.001-0.050% of N, and the rest, namely, Fe and inevitable impurities. The bar steel has a structure having a ferrite phase, and has on a surface thereof an oxided scale having a thickness of 10 μm or more. The bar steel has yield strength in an axial direction of 400 MPa or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel bar having excellent axial yield strength and a surface protected by an oxide scale, and to a method for producing the same. TECHNICAL FIELD The present invention relates to a steel bar having excellent axial yield strength and a surface protected by an oxide scale, and to a method for producing the same. [Background technology]

[0002] Cold processing of steel bars includes drawing, which utilizes strain caused by axial elongation and reduction in cross-sectional area to improve fatigue strength and yield strength, which are mechanical properties of steel. For example, Non-Patent Document 1 discloses a method for manufacturing a tube that has excellent fatigue strength and increases axial (axial) yield strength by drawing. On the other hand, drawing removes surface oxides before processing, reduces the cross-sectional area of ​​the steel bar using a die with an inner diameter smaller than the outer diameter of the steel bar after forming a lubricating film, and applies strain by drawing. In other words, the removal of surface oxides before drawing and the drawing process inevitably result in exposed metal skin after processing, and there is nothing to protect the steel bar surface. Therefore, when the steel bar comes into contact with hard objects, such as stones at the construction site or product processing equipment, dents and scratches on the surface are easily generated. In other words, conventional drawing has a problem in that it is not possible to simultaneously suppress dents and scratches on the surface that occur in the general use of steel bars and improve the axial yield strength of the steel bar.

[0003] Patent Document 1 discloses a method of forming a hard layer on the surface of a steel bar by shot peening or carburizing, and it has been reported that this treatment increases the hardness of the surface layer and improves the fatigue life. However, these methods only harden the steel bar up to about 1000 μm below the surface, so although they are effective in improving fatigue strength by suppressing initial cracks in the surface layer, they do not contribute to the axial yield strength of the entire steel bar. In other words, although these methods provide excellent fatigue strength, the yield strength of the entire steel bar is low, and there is a problem that when the entire steel bar is deformed by an external load, it will yield and deform early. In addition, although shot peening and carburizing are effective in improving fatigue strength, the metal surface remains exposed even after the treatment, and there is nothing to protect the steel bar surface. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-23399 A [Non-patent literature]

[0005] [Non-Patent Document 1] Shinzo Kobayashi, Materials Science, Vol. 22, No. 241 (1973), pp. 962-968 Summary of the Invention [Problem to be solved by the invention]

[0006] There is a demand for steel bars with increased axial yield strength to suppress deformation due to external stress loads and to improve fatigue life against stress amplitude loads. In order to improve fatigue life, it is also necessary to suppress dents due to scratches that are the starting point for crack initiation on the surface, and for steel bars used for such purposes, it is also important that the surface of the steel bar is protected from contact or collision with hard objects that cause dents and scratches.

[0007] An object of the present invention is to provide a steel bar capable of increasing the axial yield strength while suppressing depressions in the surface layer due to scratches, and a method for manufacturing the same. [Means for solving the problem]

[0008] The inventors have conducted extensive research into methods for increasing the axial yield strength of steel bars by strain and into the surface state of steel bars that can suppress surface dents and scratches. As a result, as described in detail below, they came up with the idea of ​​a method of applying strain to steel bars that can protect the surface of the steel bar from dents and scratches on the surface and that leaves the oxide scale as a protective film on the surface of the steel bar after cold working.

[0009] The present invention has been made based on the above findings, and the gist of the present invention is as follows. [1] In weight percent: C: 0.01 to 1.15%, Si: 0.01 to 2.50%, Mn: 0.01-2.50%, N: 0.001 to 0.050% The balance is Fe and unavoidable impurities. A steel bar having a structure containing ferrite phase, an oxide scale having a thickness of 10 μm or more on the surface, and an axial yield strength of 400 MPa or more. [2] Furthermore, in mass percent: Cr: 2.0% or less, The steel bar according to [1], containing one or two types selected from the following: Mo: 2.0% or less. [3] Furthermore, in mass percent: Ti: 0.50% or less, Al: 0.30% or less, V: 0.55% or less, The steel bar according to [1] or [2], containing one or more selected from the following: Nb: 0.75% or less. [4] Furthermore, in mass percent: Ni: less than 2.5% W: less than 1.0%, Cu: less than 2.5% B: 0.010% or less, Zr: 0.10% or less, Ca: 0.010% or less, Ta: 0.01% or less, REM: 0.10% or less, Mg: 0.10% or less, Sn: 0.30% or less, Sb: 0.30% or less, The steel bar according to any one of [1] to [3], containing one or more selected from the group consisting of Ag: 0.30% or less. [5] A steel bar according to any one of [1] to [4], wherein the average hardness in a region extending from a surface of the steel bar toward the center of the steel bar to 3 mm inside from the surface of the steel bar is 1.2 times or more greater than the hardness in the center of the steel bar. [6] A method for producing a steel bar according to any one of [1] to [5], After manufacturing steel bars by any one of the following methods (A), (B), or (C), A method for manufacturing a steel bar, comprising the steps of: clamping two or more tools against the circumferential surface of the steel bar at a distance G smaller than the initial outer diameter D0 of the steel bar; rotating the steel bar in the circumferential direction such that the tools come into contact with the outer periphery of the steel bar at least once during one rotation of the steel bar at a rotation angle (°) ≧ 360 / number of tools; and cold working the outer diameter of the steel bar to 0.98 or less of the initial outer diameter D0 of the steel bar.

[0010] Note (A) hot working, (B) annealing after hot working, (C) pickling after hot working, and annealing after the pickling [7] A method for manufacturing a steel bar according to [6], in which the maximum processing temperature in the cold processing of the steel bar is 300°C or less. [8] A method for manufacturing a steel bar according to [6] or [7], in which after the cold working, heat treatment is performed by holding the temperature at or below 300°C for 300 seconds or more and 3600 seconds or less. Effect of the Invention

[0011] According to the present invention, a steel bar product can be obtained which has high axial yield strength and is capable of suppressing surface dents due to scratches. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a graph showing the relationship between the surface oxide scale thickness and scratch depth. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a method for producing a steel bar. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described below.

[0014] First, the reasons for limiting the composition of the steel bar of the present invention will be described. Unless otherwise specified, hereinafter, mass% will simply be abbreviated as %.

[0015] C: 0.01 to 1.15% C is important for improving the strength and fatigue strength properties of steel, and is also an element necessary for forming cementite. Therefore, it is necessary to contain 0.01% or more. From the viewpoint of stably obtaining high strength and fatigue strength, the C content is preferably 0.05% or more. However, if it is contained in excess, the residual austenite phase increases, reducing the yield strength and fatigue strength. Therefore, the C content is set to 1.15% or less. From the viewpoint of stably obtaining high strength and fatigue strength, the C content is preferably 0.60% or less.

[0016] Silicon: 0.01 to 2.50% Since Si has a deoxidizing effect on steel, it is effective to include an appropriate amount of Si in molten steel. It is also necessary to include Si because it is effective in improving the strength properties of steel. However, if a large amount of Si remains in the steel, it impairs cold workability and low-temperature toughness. Therefore, the Si content is set to 2.50% or less. From the viewpoint of suppressing a decrease in toughness due to excessive Si remaining in the steel while obtaining a sufficient deoxidizing effect, the Si content is preferably 2.00% or less. On the other hand, excessive reduction of Si after deoxidization leads to an increase in manufacturing costs, so the Si content is set to 0.01% or more.

[0017] Mn: 0.01 to 2.50% In order to improve the strength properties of steel, Mn must be contained at 0.01% or more. Therefore, the Mn content is set to 0.01% or more. The Mn content is preferably set to 0.10% or more. On the other hand, since Mn is a strong austenite phase forming element, if Mn is contained in excess, the residual austenite phase in the steel increases, and the yield strength and fatigue strength decrease. Therefore, the Mn content is set to 2.50% or less. In order to obtain a specified structure while improving the strength properties, the Mn content is preferably set to 0.80% or less.

[0018] N: 0.001 to 0.050% In order to obtain a fine structure and strength properties, the N content must be 0.001% or more. The N content is preferably 0.005% or more. However, if the N content is excessive, bubbles will form in the steel, so the N content should be 0.050% or less. Processing to extremely low N levels takes time and costs money. From the viewpoint of stably obtaining a fine structure without bubbles, the N content should be 0.010% or less.

[0019] The balance is Fe and unavoidable impurities. Examples of unavoidable impurities include P: 0.05% or less, S: 0.05% or less, and O: 0.01% or less. P, S, and O are impurities that are inevitably mixed in during refining. If the remaining amounts of these elements as impurities are too high, various problems may occur, such as reduced hot workability, corrosion resistance, and low-temperature toughness. Therefore, it is preferable to control the amounts of P: 0.05% or less, S: 0.05% or less, and O: 0.01% or less, respectively.

[0020] In addition to the above-mentioned component composition, the present invention may contain the following elements as necessary.

[0021] Contains one or two of the following: Cr: 2.0% or less, Mo: 2.0% or less Cr:2.0% or less Cr improves the strength properties of steel and is effective in improving corrosion resistance and wear resistance, so when Cr is contained, it is preferable that the Cr content is 0.05% or more. It is more preferable that the Cr content is 0.5% or more. On the other hand, if Cr is contained in excess, the hardness increases and the cold workability decreases, so when Cr is contained, the Cr content is 2.0% or less. To obtain the effect of improving corrosion resistance and wear resistance and appropriate cold workability, the Cr content is preferably 1.3% or less.

[0022] Mo: 2.0% or less Mo is effective in improving high-temperature strength properties and corrosion resistance, so if Mo is contained, it is preferable that Mo be contained in an amount of 0.05% or more. On the other hand, if Mo is contained in an excessive amount, the hardness increases and the cold workability decreases, so if Mo is contained, the Mo content is set to 2.0% or less. From the viewpoint of obtaining high-temperature strength properties, corrosion resistance, and appropriate cold workability, the Mo content is preferably set to 1.5% or less.

[0023] The present invention may further contain the following elements as necessary.

[0024] One or more selected from the following: Ti: 0.50% or less, Al: 0.30% or less, V: 0.55% or less, Nb: 0.75% or less When contained in an appropriate amount, Ti, Al, V, and Nb form nitrides or carbides and are effective in refining the structure, and can be contained as necessary.

[0025] Ti: 0.50% or less When Ti is contained, the Ti content is preferably 0.001% or more. On the other hand, when Ti is contained, the Ti content is set to 0.50% or less in order to prevent a decrease in toughness.

[0026] Al: 0.30% or less When Al is contained, the Al content is preferably 0.001% or more. On the other hand, when Al is contained, the Al content is set to 0.30% or less in order to prevent a decrease in toughness.

[0027] V: 0.55% or less When V is contained, the V content is preferably 0.01% or more. On the other hand, when V is contained, the V content is set to 0.55% or less in order to prevent a decrease in toughness.

[0028] Nb: 0.75% or less When Nb is contained, the Nb content is preferably 0.01% or more. On the other hand, when Nb is contained, the Nb content is set to 0.75% or less in order to prevent a decrease in toughness.

[0029] The present invention may further contain the following elements as necessary.

[0030] One or more selected from the following: Ni: less than 2.5%, W: less than 1.0%, Cu: less than 2.5%, B: 0.010% or less, Zr: 0.10% or less, Ca: 0.010% or less, Ta: 0.01% or less, REM: 0.10% or less, Mg: 0.10% or less, Sn: 0.30% or less, Sb: 0.30% or less, Ag: 0.30% or less Ni: Less than 2.5% Ni is effective in improving the toughness of steel. When Ni is contained, it is preferable that Ni is contained in an amount of 0.01% or more. From the viewpoint of stably obtaining excellent toughness, yield strength, and fatigue strength, the Ni content is more preferably 0.05% or more. On the other hand, if Ni is contained in excess, the residual austenite phase increases, and the yield strength and fatigue strength decrease. Therefore, when Ni is contained, the Ni content is made less than 2.5%. From the viewpoint of stably obtaining excellent toughness, yield strength, and fatigue strength, the Ni content is preferably 0.8% or less.

[0031] W: Less than 1.0%, Cu: Less than 2.5% W and Cu improve the corrosion resistance of steel. When W is contained, the W content is preferably 0.01% or more. When Cu is contained, the Cu content is preferably 0.01% or more. On the other hand, if the content of each element is high, it may cause deterioration of the surface skin and defects during hot forming. Therefore, when W is contained, the W content is less than 1.0%. The W content is preferably 0.1% or less. When Cu is contained, the Cu content is less than 2.5%. The Cu content is preferably 1.5% or less.

[0032] B: 0.010% or less Even if a very small amount of B is contained, it affects the workability and surface scale during hot forming, and helps to suppress surface defects. Therefore, if B is contained, the B content is preferably 0.001% or more. However, excessive content may worsen surface defects. Therefore, if B is contained, the B content is 0.010% or less. The B content is preferably 0.005% or less.

[0033] Zr: 0.10% or less Even if a very small amount of Zr is contained, it affects the workability and surface scale during hot forming, and helps to suppress surface defects. Therefore, if it is contained, the Zr content is preferably 0.01% or more. However, excessive content may worsen surface defects. If Zr is contained, the Zr content should be 0.10% or less. It is more preferable that the Zr content is 0.03% or less.

[0034] Ca: 0.010% or less When a very small amount of Ca is contained, it affects the workability and surface scale during hot forming, and helps to suppress surface defects. Therefore, when it is contained, the Ca content is preferably 0.001% or more. However, excessive content may worsen surface defects. When Ca is contained, the Ca content is 0.010% or less. The Ca content is preferably 0.005% or less.

[0035] Ta: 0.01% or less Ta, when contained in very small amounts, affects workability and surface scale during hot forming, and helps to suppress surface defects. Therefore, if contained, the Ta content is preferably 0.001% or more. However, excessive inclusion may worsen surface defects. If Ta is contained, the Ta content is 0.01% or less. The Ta content is preferably 0.005% or less.

[0036] REM: 0.10% or less Even if REM is contained in a very small amount, it affects the workability and surface scale during hot forming, and helps to suppress surface defects. Therefore, if REM is contained, the REM content is preferably 0.001% or more. However, excessive content may worsen surface defects, so if REM is contained, the REM content should be 0.10% or less. The REM content is preferably 0.005% or less.

[0037] Mg: 0.10% or less Even if a very small amount of Mg is contained, it affects the workability and surface scale during hot forming, and helps to suppress surface defects. Therefore, if Mg is contained, the Mg content is preferably 0.001% or more. However, excessive content may worsen surface defects. If Mg is contained, the Mg content should be 0.10% or less. The Mg content is preferably 0.005% or less.

[0038] Sn: 0.30% or less, Sb: 0.30% or less, Ag: 0.30% or less When Sn, Sb, and Ag are contained in small amounts, the corrosion resistance performance is improved. There is no need to set a lower limit for the content, but when contained, the Sn, Sb, and Ag content should be 0.0001% or more to improve the corrosion resistance performance. On the other hand, if the content is too high, the hot workability is reduced. Therefore, when contained, the Sn, Sb, and Ag content should be 0.30% or less.

[0039] Next, the structure of the steel bar in the present invention will be described.

[0040] The structure of the present invention has a structure having a ferrite phase. The ferrite phase refers to a structure having a single ferrite phase, a bainite phase, or a bainite phase in the ferrite phase. The structure also includes a structure having a ferrite phase and a cementite phase (including a pearlite phase in which the ferrite phase and the cementite phase are layered). A steel bar having these structures does not have a high axial yield strength when cooled after hot working (including hot rolling) or when treated by annealing heat treatment, but when cold working is performed, the yield strength can be increased by dislocation strengthening due to plastic strain. Furthermore, it can have a high surface hardness, which is also preferable for improving fatigue strength. There is no particular restriction on the area fraction of the ferrite phase, but it is preferable for the ferrite phase fraction to be 50% or more because the workability during cold working is good. The area fraction of the cementite phase is not particularly limited, but it is preferable that it is 5% or more from the viewpoint of obtaining high strength and high hardness. In addition, from the viewpoint of excellent toughness and cold workability, the area fraction of the cementite phase is preferably 50% or less. In addition, it is also preferable to contain retained austenite in a structure other than the above-mentioned structure. However, if the area ratio of the retained austenite phase exceeds 10%, it adversely affects fatigue properties, so that the area ratio is preferably 10% or less.

[0041] The method of measuring the structure is as follows. The material before cold rolling and processing is mirror-polished and etched with an acid such as Nital or Villela etchant. The structure containing the ferrite phase or the ferrite phase and the cementite phase can be confirmed by an optical microscope, and the black-colored area in the image observed with the optical microscope is measured as cementite. The observation magnification is 100 to 400 times, and the area fraction can be measured with high accuracy when 50 or more ferrite grains, or ferrite grains and pearlite grains, can be observed in the field of view. For the retained austenite phase, the peaks of the body-centered cubic lattice of the ferrite phase and the face-centered cubic lattice of the austenite phase are separated by X-ray diffraction for the test piece after mirror polishing and electrolytic polishing, and the volume fraction is measured by comparing the intensity ratio of these two peaks, and this volume fraction is taken as the area fraction.

[0042] In the steel bar of the present invention, the same structure is obtained before and after cold working. Moreover, the structure of the steel bar of the present invention can be controlled by adjusting the composition of the components.

[0043] In the steel bar of the present invention, the axial yield strength is set to 400 MPa or more. Normally, a soft structure containing a ferrite phase does not reach an axial yield strength of 400 MPa without cold working. Therefore, dislocation strengthening by cold working is required to obtain a high axial yield strength of 400 PMa or more. There is no upper limit to the axial yield strength, but if the strength is too high, delayed fracture occurs, so it is preferably set to 870 MPa or less.

[0044] The axial yield strength is measured in the range from the surface of the steel bar to a position 3 mm inward in the radial direction of the steel bar. In many cases, the stress applied by an external force to the steel bar is bending stress. The bending stress is the largest on the outer surface of the steel bar, and the highest tensile stress occurs on the outer surface side of the bend. In other words, if the axial yield strength is increased in the range from the surface of the steel bar to a position 3 mm inward, the steel bar will have excellent strength characteristics that can withstand bending stress. Similarly, since the stress amplitude is the largest on the surface of the steel bar, it is effective to increase the axial yield strength in the range from the surface to a position 3 mm inward in terms of improving fatigue strength characteristics. Note that conventional technologies such as nitriding and shot peening can only increase the hardness to a depth of 1000 μm from the surface, and are not effective enough in suppressing deformation due to bending stress. Therefore, by increasing the axial yield strength in the range from the surface to a position 3 mm inward, a steel bar with excellent strength characteristics that can withstand bending stress can be obtained.

[0045] Axial yield strength can be measured by taking a round bar-shaped tensile test piece from the region from the surface of the steel bar to a position 3 mm inward in the radial direction of the steel bar. Alternatively, a cylindrical tensile test piece cut from the above region at a position 3 mm from the surface of the steel bar, or a circular arc-shaped plate tensile test piece cut in the axial direction from the cylindrical evaluation portion, may be used. The tensile test can be performed according to the metallic material tensile test method described in JIS. Z 2241:2011. The axial yield strength of 400 MPa or more is not limited in the depth direction from the surface of the steel bar, and may be up to the center of the steel bar. In order to obtain sufficient strength and fatigue properties, it is preferable that the axial yield strength at a depth of 3 mm or more from the surface layer is 400 MPa or more.

[0046] The steel bar of the present invention has an oxide scale having a thickness of 10 μm or more on the surface, for the following reasons.

[0047] FIG. 1 shows the effect of oxide scale in suppressing dents and scratches on the surface of a steel bar, and further shows the effect of cold working in suppressing scratches. The steel bar used in the test shown in FIG. 1 is a steel bar obtained by heating a slab (bloom) consisting of, by mass%, 0.15-0.55% C, 0.1-0.40% Si, 0.25-0.70% Mn, 0.003-0.010% N, with the remainder being iron and unavoidable impurities, at 1100-1250°C for 1 hour, hot rolling, and manufacturing a steel bar having a specified outer diameter, and then performing the above-mentioned cold working to make the axial yield strength 400 MPa or more. For comparison, steel bars not subjected to cold working and steel bars in which all oxide scale was removed by machining or pickling before cold working and the axial yield strength was made 400 MPa or more by cold working were also prepared, and tests were performed to measure the thickness of the oxide scale and the depth of scratches at the same time. The one in which all oxide scale was removed by machining or pickling before cold working corresponds to the level of 0 μm of oxide scale in FIG. 1. After cold working, the steel bars were cut into rings in the axial direction, embedded in resin so that the cut cross section would be the observation surface, and polished to a mirror finish before measuring the thickness of the oxide scale on the steel bars. The oxide scale thickness was measured by observation using an optical microscope. For bars where the boundary between the oxide scale and the base metal was difficult to distinguish, oxygen analysis was performed using SEM-EDS, and the area where 400 mass ppm or more of oxygen had infiltrated into the base metal was defined as the oxide scale, and the thickness was measured.

[0048] Next, a needle made of ultra-hard material was applied to the surface of the steel bar after cold working, a weight of 7 kg was placed on the needle and the needle was scanned in the axial direction to give a scratch, and the depth of the scratch was evaluated, and this depth was taken as the dent depth due to the scratch. The measurement of the dent depth due to the scratch was performed by cutting the steel bar in a direction perpendicular to the scratch, i.e., in the circumferential direction of the steel bar, embedding the sample in resin so that the cross section perpendicular to the axial direction was the observation surface, mirror polishing, and observing the scratched part on the steel bar surface with an optical microscope. The distance from the bottom of the dent made by the needle to the steel bar surface was taken as the dent depth due to the scratch. From Figure 1, it can be seen that the depth of the scratch can be significantly suppressed by combining a material with an oxide scale thickness of 10 μm or more and an axial yield strength of 400 MPa or more by the above-mentioned cold working (with cold working). Therefore, the thickness of the oxide scale is set to 10 μm or more. The thickness of the oxide scale is preferably 20 μm or more. The thicker the oxide scale, the greater the scratch-inhibiting effect, so there is no upper limit, but a thickness of 100 μm or less is preferable because too thick oxide scale peels off and falls off. More preferably, the thickness is 50 μm or less. In addition, as for the chemical composition of the oxide scale, if it contains 400 mass ppm or more of oxygen, it is preferable that it contains 400 mass ppm or more of oxygen, since it exhibits a scratch-inhibiting effect. In addition, regardless of the heating before hot rolling or the atmosphere during rolling, the oxide scale exhibits a scratch-inhibiting effect if it is 10 μm or more thick, but it is preferable that the heating temperature in the hot rolling performed for the purpose of increasing the adhesion between the oxide scale and the steel bar surface while keeping the thickness of the oxide scale within a preferred range and the annealing heat treatment performed thereafter is 900 ° C to 1300 ° C.

[0049] The average hardness in the area from the surface of the steel bar toward the center of the steel bar to 3 mm inside from the surface of the steel bar is 1.2 times or more the hardness of the center of the steel bar. In order to suppress deformation due to external load, it is important to increase the hardness of the surface of the steel bar, where the stress during bending deformation of the steel bar is the largest. On the other hand, if the hardness of the steel bar from the surface to 3 mm is 1.2 times or more than that of the center of the steel bar, the toughness of the center of the steel bar is improved, and even if a crack occurs from the surface of the steel bar, the propagation is suppressed and a fracture accident is prevented, which is preferable. In addition, obtaining a high surface hardness is also preferable in terms of improving fatigue strength. The hardness from the surface to a position of 3 mm from the surface was calculated by grinding the surface of the steel bar cut into rings with a grindstone, and measuring the hardness at a pitch of 0.5 to 1.0 mm from the surface to a position of 3 mm, and averaging the values. Since the hardness varies, the hardness of the center of the steel bar was measured at three or more points and the average value was calculated. Various hardness tests such as Brinell hardness test, Rockwell hardness test, Vickers hardness test, and Shore hardness test can be used to measure hardness.

[0050] Next, a method for producing a steel bar according to the present invention will be described.

[0051] First, a steel material having the above steel composition is prepared. Various melting processes can be applied to the production of steel, and there is no limitation. For example, when manufacturing by electrically melting iron scrap or a lump of each element, a vacuum melting furnace or an atmospheric melting furnace can be used. When using molten pig iron by the blast furnace method, an Ar-O2 mixed gas bottom blowing decarburization furnace or a vacuum decarburization furnace can be used. The melted material is solidified by static casting or continuous casting to form an ingot, slab, or bloom, and then cold working is performed after forming a steel bar material using one of the following methods (A), (B), or (C). (A) Hot working, (B) annealing after hot working, (C) pickling after hot working, and annealing after the pickling. Note that hot working also includes hot rolling. In addition, as in the above (B) and (C), it is preferable to perform annealing heat treatment before cold working on the steel bar after hot working, because this homogenizes the structure and removes residual stress. It is not preferable to perform annealing after cold working, which was performed before the cold working, since this reduces the yield strength of the steel bar. Furthermore, if pickling is performed after cold working, it becomes impossible to ensure a predetermined oxide scale, so it is also not preferable to perform pickling after cold working.

[0052] Cold working of steel bars Cold working of steel bars is performed by clamping two or more tools against the circumferential surface of the steel bar at a distance G smaller than the initial outer diameter D0 of the steel bar, and rotating the steel bar in the circumferential direction so that the tools come into contact with the outer periphery of the steel bar at least once during one rotation of the steel bar, with the rotation angle (°) ≧ 360 / number of tools, so that the outer diameter of the steel bar after cold working is 0.98 or less relative to the initial outer diameter D0 of the steel bar.

[0053] In the present invention, by applying two or more tools to the outer periphery of the steel bar and rotating the steel bar in the outer periphery direction of the steel bar to reduce the outer diameter, it is possible to improve the axial yield strength of the steel bar while maintaining the oxide scale on the surface of the steel bar at a thickness of 10 μm or more.

[0054] This processing method will be explained based on the drawings. Figure 2(a) is a cross-sectional view when there are two tool contact parts, and Figure 2(b) is a cross-sectional view when there are three tool contact parts. D0 in the figure 2 indicates the initial outer diameter of the steel bar 1, and G in the figure 4 indicates the tool interval. At the point on the pass line where the tool interval (G = GAP) is the narrowest in the axial direction, when a tool cross section perpendicular to the pass line is drawn, the radius of a perfect circle (a perfect circle inscribed in the interval between the tools 3) that is tangent to all the tools 3 used for diameter reduction is geometrically determined as 1 / 2G. Also, the arrow 5 on the tool 3 in Figure 2 indicates the direction in which the tool 3 is moving, and the arrow 6 in the steel bar 1 indicates the direction in which the steel bar 1 rotates as the tool 3 moves. In the cold working of the present invention, the tool interval G is small relative to the initial outer diameter D0 of the steel bar, and the tool 3 comes into contact with the outer periphery of the steel bar at least once due to the movement of the tool 3 or the movement and rotation of the steel bar 1; that is, when the steel bar 1 is rotated in the circumferential direction of the steel bar at a rotation angle (°) ≧ 360 / number of tools with a tool interval G narrower than the initial outer diameter D0 of the steel bar, the outer periphery of the steel bar is cold worked at least once and reduced in diameter. The steel bar can obtain excellent axial yield strength by being subjected to diameter reduction processing in the cold working form of the present invention. In addition, the cold working makes it easier to obtain high surface hardness, which is also preferable in terms of improving fatigue strength.

[0055] In addition, in the cold working of the present invention, there is little sliding between the surface of the tool 3 and the surface of the steel bar, and the tool 3 and the surface of the steel bar come into contact while moving in the same direction, so that it is possible to maintain an oxide scale on the surface with a thickness of 10 μm or more even after cold working. The tool 3 needs to move in order to rotate the steel bar 1. For example, a parallel movement in the circumferential direction of the steel bar can be performed. A method of rotating the tool 3 and bringing it into contact is preferable. In normal cold working of the steel bar 1, as represented by cold drawing, the position of the tool 3 (die) that performs the cold working is fixed, so the steel bar 1 that is drawn and deformed and the tool surface do not move in the same direction. Therefore, the surface of the steel bar is always deformed while sliding on the tool, and severe seizure occurs. Therefore, in order to suppress seizure, it is essential to remove the oxide scale on the surface of the steel bar, and it is not possible to leave an oxide scale with a thickness of 10 μm or more on the surface of the steel bar after cold working. Therefore, in the present invention, processing cannot be performed by cold drawing.

[0056] The tool 3 and the outer periphery of the steel bar need to come into contact with each other at least once during one rotation of the steel bar 1, but they may come into contact with each other at least twice. To bring the tool 3 into contact with the outer periphery of the steel bar at least once, the rotation angle (°) of the steel bar 1 in the circumferential direction of the steel bar 1 should be ≧360 / number of tools. There is no upper limit to the rotation angle. Since the steel bar 1 is reduced in diameter from the second contact onwards, the steel bar 1 and the tool 3 may not come into proper contact with each other with the same tool interval G. Therefore, in order to bring the outer periphery of the steel bar into proper contact with each other, it is advisable to adjust the tool interval G from the second contact onwards between the steel bar surface and the tool 3. As shown in FIG. 2, by bringing the outer periphery of the steel bar 1 into contact with the tool 3 intermittently or continuously at least once during one rotation of the steel bar 1, a strain is applied to the steel bar 1, and as a result, the axial yield strength of the steel bar 1 is increased. This is also a useful method for increasing the surface hardness, and is also preferable in terms of improving fatigue properties.

[0057] There is no limitation to the tool shape in FIG. 2, and it is sufficient that the diameter of the steel bar 1 can be reduced by an appropriate tool interval G. For example, rolls may be used as the tool 3, and the steel bar 1 can be easily cold-worked to reduce the diameter by sandwiching the steel bar 1 between two or more rolls arranged in the circumferential direction of the steel bar with a roll interval G1 and rotating the rolls. Furthermore, if the rotation axis of the roll is inclined within 90° with respect to the rotation axis of the steel bar 1, the steel bar 1 advances in the axial direction of the steel bar while undergoing cold working, and thus continuous cold working can be easily performed. In addition, continuous processing using these rolls can be performed by, for example, appropriately changing the roll interval G1 with respect to the direction of advancement of the steel bar, and using different roll intervals G1 for the first and second cold working. Although the equipment becomes complicated, it is preferable to use three or more rolls because the whirling of the steel bar 1 during cold working can be suppressed and stable cold working can be achieved. The outer diameter of the steel bar after cold working in the present invention varies depending on the tool interval G, but excellent yield strength can be obtained when the outer diameter of the steel bar after cold working is 0.98 or less with respect to the initial outer diameter D0 of the steel bar. Since the outer diameter of the steel bar after cold working for an excessively small initial outer diameter D0 of the steel bar may cause seizure or scale peeling due to an increase in forming load, it is preferable that the outer diameter of the steel bar after cold working for the initial outer diameter D0 of the steel bar is 0.75 or more. In addition, since it is difficult to obtain a high hardness distribution in the surface layer of the steel bar with respect to an excessively large initial outer diameter D0 of the steel bar, it is preferable that the outer diameter of the steel bar after cold working is 0.95 or less.

[0058] The processing temperature in cold working must be controlled so that accumulated dislocations do not disappear. As long as the dislocations do not disappear, there is no problem with heat generation when heating or increasing the processing speed, but it is preferable to control the maximum temperature reached by the steel bar 1 during processing (maximum processing temperature) to 300°C or less. This temperature is obtained by measuring the outer surface temperature of the steel bar immediately after cold working. Either a non-contact or contact thermometer can be used to measure the temperature.

[0059] In the present invention, heat treatment may be performed within a range in which dislocations do not disappear after cold working. By performing heat treatment, residual stress after cold working is reduced, and fatigue strength can be improved more easily, so this is preferable. The upper limit of the heat treatment temperature is preferably 300°C or less, which is a temperature at which dislocations disappear and the axial yield strength does not decrease. In addition, the holding time at the above temperature is preferably 300 seconds or more and 3600 seconds or less. EXAMPLES

[0060] The present invention will be described below with reference to examples.

[0061] Steels having the chemical compositions of steel types A to N shown in Table 1 were melted in a vacuum melting furnace.

[0062] [Table 1]

[0063] The materials with chemical compositions A to N were heated to 1200°C or higher, and then hot-rolled into a round bar shape with a diameter of 60 mm. Some of the round bar steel was reheated by holding it at 950°C for 1 hour as an annealing heat treatment, and then annealed by slow cooling in a furnace before cold working.

[0064] Steel types A to N were subjected to only hot rolling, or hot rolling followed by annealing, or hot rolling followed by pickling, to produce steel bars that were annealed and used as test materials for cold working. As comparative materials, the steel bars produced above were also prepared by removing the oxide scale with acid.

[0065] Table 2 shows the cold working conditions and the evaluation results of the mechanical properties.

[0066] Cold working was performed using a method using three roll tools, which is one of the forms of the cold working method of the present invention. For comparison, cold drawing was also performed, in which hot rolled steel bars and annealed steel bars were used as materials, and the oxide scale on the surface was completely removed with acid, and then a chemical conversion coating for lubrication was applied to the surface of the steel bars, and drawing was performed one to three times to reduce the outer diameter from Φ58 mm to Φ48 mm.

[0067] In the cold working of the present invention, three roll tools were arranged at a pitch of 120° around the outer circumference of the steel bar, and the roll gap G1 was adjusted to change the number of contacts between the tool and the steel bar surface from 1 time (1 contact between the steel bar surface and the tool is counted as 1 time) to 3 times, thereby changing the outer diameter of the steel bar from Φ58 mm to Φ48 mm. As a comparative material, a material that had been subjected to cold drawing was prepared.

[0068] The working temperatures during cold drawing and the cold working of the present invention were measured with a non-contact radiation thermometer immediately after working. In some conditions, the steel was heated to 950°C after cold working as an annealing heat treatment, held for 1 hour, and then furnace-cooled. In some conditions, the steel was subjected to a heat treatment in which the heating temperature and holding time were controlled, and then left to cool after the heat treatment.

[0069] As a comparative material, a material that was partially cold worked and then annealed was prepared.

[0070] After cold working, the steel bars were mirror-polished in a 300 μm × 300 μm field of view at a position 3 mm from the surface toward the center of the steel bar, and then observed with an optical microscope after nital etching to identify the microstructure. The observation surface was a cross section perpendicular to the axial direction. The microstructure was identified by observing with an optical microscope at a magnification of 100 to 400 times so that a total of 50 or more ferrite grains or ferrite grains and cementite grains were visible.

[0071] In addition, the retained austenite phase fraction was measured by X-ray in a measurement range of 2 mm x 2 mm within a region 3 mm from the surface of the steel bar toward the center of the steel bar. The method for preparing the test material used in the X-ray measurement of the retained austenite phase fraction is explained below. The test material was prepared by taking a 2 mm square plate sample from a position up to 3 mm toward the center of the steel bar, with the vertical cross section of the steel bar as the target surface, and preparing the measurement surface by mirror polishing and then electrolytic polishing. After preparation, the test piece was subjected to X-ray diffraction with a 1.5 mm slit width to measure the bcc and fcc peaks, and the fcc fraction in the bcc was calculated by comparing the intensity ratio, which was taken as the retained austenite phase fraction.

[0072] As a result of the structural observation, it was found that steel types H to K had voids in the steel due to graphite or nitrogen gas, or cracks occurred during cold working, and they could not be finished into the specified bar shape, so further investigation was discontinued.

[0073] To evaluate the mechanical properties of steel types A to G and L to N, the yield strength in the axial direction of the steel bar and the inner and outer hardness ratio of the steel bar were compared. Yield strength was measured by taking a Φ3mm round bar tensile test piece from a position 3mm from the surface of the steel bar toward the center of the steel bar and conducting a tensile test at a tension speed of 1mm / min. The yield strength was defined as 0.2% proof stress.

[0074] The hardness distribution of the cross section of the steel bar was evaluated using a Vickers hardness tester. The steel bar after cold working was cut in the axial direction, the cross section was polished, and the hardness was measured at 0.5 mm intervals within a range of 3 mm from the outer surface to the center of the steel bar. The measurements were also carried out at three positions in the circumferential direction of the steel bar. The average hardness measured from the surface of the steel bar to a position 3 mm away was divided by the hardness at the center of the steel bar to obtain the inner / outer hardness ratio of the steel bar.

[0075] The effect of suppressing scratches on the surface of steel bars was evaluated by measuring scale thickness and a scratch test. In this evaluation, first, the steel bar after cold working was cut into rings in the axial direction, and the surface layer was embedded in resin so that the cut cross section became the target surface, and then the thickness of the oxide scale was measured after embedding it in resin and polishing it to a mirror surface. The thickness of the oxide scale was observed and measured with an optical microscope. For specimens in which the boundary between the oxide scale and the base metal was difficult to distinguish, oxygen analysis was performed using SEM-EDS, and the thickness was measured by defining the region in which oxygen infiltrated the base metal at 400 mass ppm or more as oxide scale. Next, a needle made of ultra-hard material was placed on the surface of the steel bar after cold working, and a 7 kg weight was placed on the needle and scanned in the axial direction to give scratches, and the depth of the scratches was evaluated. The scratch depth was measured by cutting the steel bar in a ring in the direction perpendicular to the scratches, i.e., in the circumferential direction of the steel bar, embedding the sample in resin so that the cross section perpendicular to the axial direction became the target surface, polishing it to a mirror surface, and observing the surface scratches with an optical microscope. The scratch depth was evaluated by measuring the distance between the bottom of the dent made by the needle and the surface of the steel bar.

[0076] [Table 2]

[0077] From the results in Table 2, when the cold working of the present invention was performed on the steel bar after hot rolling or annealing heat treatment, an excellent axial yield strength of 400 MPa or more was obtained, and further, an oxide scale of 10 μm or more was obtained on the surface of the steel bar after cold working, and excellent scratch resistance, which is a scratch depth of 100 μm or less, was obtained. [Explanation of symbols]

[0078] 1 steel bar 3 tools 5 Tool movement direction 6 Rotation direction of steel bar D0 Initial outer diameter of steel bar G Tool spacing 1 / 2G The radius of the perfect circle that is geometrically in contact with all the tools used for diameter reduction

Claims

1. In mass percent, C: 0.01-1.15%, Si: 0.01-2.50%, Mn: 0.01 to 2.50%, N: 0.001 to 0.050%; The balance is Fe and unavoidable impurities, It has a structure having a ferrite phase, has an oxide scale having a thickness of 10 μm or more on the surface, and has an axial yield strength of 400 MPa or more; A steel bar having an average hardness in a region extending from a surface of the steel bar toward the center of the steel bar to an inner region of 3 mm from the surface of the steel bar, which is 1.2 times or more harder than the hardness of the center of the steel bar.

2. Further, in mass percent, Cr: 2.0% or less, 2. The steel bar according to claim 1, further comprising one or two selected from the following: Mo: 2.0% or less.

3. Further, in mass percent, Ti: 0.50% or less, Al: 0.30% or less, V: 0.55% or less, The steel bar according to claim 1 or 2, further comprising one or more selected from the following: Nb: 0.75% or less.

4. Further, in mass percent, Ni: less than 2.5% W: less than 1.0% Cu: less than 2.5% B: 0.010% or less, Zr: 0.10% or less, Ca: 0.010% or less, Ta: 0.01% or less, REM: 0.10% or less, Mg: 0.10% or less, Sn: 0.30% or less, Sb: 0.30% or less, The steel bar according to any one of claims 1 to 3, containing one or more selected from the following: Ag: 0.30% or less.

5. A method for producing a steel bar according to any one of claims 1 to 4, After producing a steel bar by any one of the following methods (A), (B), or (C), A method for manufacturing a steel bar, comprising the steps of: clamping two or more tools against a circumferential surface of the steel bar at a distance G smaller than an initial outer diameter D0 of the steel bar; rotating the steel bar in the circumferential direction such that the tools come into contact with the outer periphery of the steel bar at least once during one rotation of the steel bar at a rotation angle (°) ≧ 360 / number of tools; and cold working the outer diameter of the steel bar to 0.98 or less of the initial outer diameter D0 of the steel bar. Note (A) hot working, (B) annealing after hot working, (C) pickling after hot working and annealing after the pickling

6. The method for producing a steel bar according to claim 5, wherein the maximum working temperature in the cold working of the steel bar is 300°C or less.

7. The method for producing a steel bar according to claim 5 or 6, wherein after the cold working, a heat treatment is performed by holding the steel at 300°C or less for 300 seconds or more and 3600 seconds or less.

Citation Information

Patent Citations

  • Production of rod steel without thermal refining

    JP1979077217A

  • Manufacture of high and medium carbon hot rolled steel rod

    JP1986044123A

  • Manufacture of unrefined rolled steel bar

    JP1986264130A

  • Manufacture of medium carbon steel for cold working having small deformation resistance

    JP1987188723A

  • Manufacture of fine-grained steel

    JP1987274024A